Applied behavior analytic intervention for autism in early childhood: Meta-analysis, meta-regression and dose–response meta-analysis of multiple outcomes - Virués-Ortega, Javier (Clinical psychology review, 2010)
A number of clinical trials and single-subject studies have been published measuring the effectiveness of long-term, comprehensive applied behavior analytic (ABA) intervention for young children with autism. However, the overall appreciation of this literature through standardized measures has been hampered by the varying methods, designs, treatment features and quality standards of published studies. In an attempt to fill this gap in the literature, state-of-the-art meta-analytical methods were implemented, including quality assessment, sensitivity analysis, meta-regression, dose–response meta-analysis and meta-analysis of studies of different metrics. Results suggested that long-term, comprehensive ABA intervention leads to (positive) medium to large effects in terms of intellectual functioning, language development, acquisition of daily living skills and social functioning in children with autism. Although favorable effects were apparent across all outcomes, language-related outcomes (IQ, receptive and expressive language, communication) were superior to non-verbal IQ, social functioning and daily living skills, with effect sizes approaching 1.5 for receptive and expressive language and communication skills. Dose-dependant effect sizes were apparent by levels of total treatment hours for language and adaptation composite scores. Methodological issues relating ABA clinical trials for autism are discussed.